Optimization of the osmotic dehydration process for improving the quality of vacuum-fried “Vinh Chau” shallots at the pilot stage - Ngô Văn Tài; Nguyễn Minh Thủy (Acta Scientiarum Polonorum Technologia Alimentaria, 2023)
1School of Food Industry, King Mongkut’s Institute of Technology Ladkrabang, Bangkok, Thailand 2Institute of Food and Biotechnology, Can Tho University, Vietnam
Keywords: Garlic and Onion Studies; Food Drying and Modeling; Flowering Plant Growth and Cultivation